Perbedaan Karakter Siswa Pada Pembelajaran Matematika Berorientasi Alquran Berbasis Gender - Fenny Anggraini (Pusat Studi Gender dan Anak, 2020)
Character is a person's attitude or actions that are very strong and difficult to remove that are formed from the environment. Each student has a different character both male and female students. This journal aims to determine the differences in the character of male and female students in the learning of mathematics oriented in the quranic proposition. The research instrument used was the observation sheet. The research subjects were 6 students consisting of 3 male students and 3 female students. The methodology used is descriptive quantitative method. This study found that female students' character was higher than male students. The characters of male students get a percentage of 82.82% while those of female students are 86.68%.